(untitled) (Stavební obzor - Civil Engineering Journal, 2019)
In order to study the fatigue properties of polyurethane cement (PUC), the newly bridge reinforcement material, three different densities of PUC beams were tested. The studies indicate that the fatigue life of PUC material obeys two parameters Weibull distribution, and the double logarithm fatigue equation with different failure probability is established by this mathematical model. The fatigue life equations of the PUC with three different densities (PUC1500, PUC1200 and PUC800) were established when the failure rate was 0.5. The fatigue life of PUC1500 is the largest, and the fatigue life of PUC material decreases with the decrease of its density. Under the action of bending fatigue load, the fatigue strain of PUC material can be divided into three phases.